Recent advances in the development of sunlight-driven hollow structure photocatalysts and their applications. Issue 36 (28th September 2015) - Nguyen, Chinh Chien; Vu, Nhu Nang; Do, Trong-On
<x xml:space="preserve">Abstract</x> This review highlights the recent development of sunlight-driven hollow-structure photocatalysts for solar fuel production and environmental remediation.